Plancglued wood construction with prestressed non-metallic fittings - Surmai, Mykhailo (Видавництво Львівської політехніки, 2013)
In the article is proposed a methods of anchoring and testing of prestressed nonmetallic reinforcement in timber beams. Offer examples of principal model and recommendations.
Keywords: fiberglass plastic; fiberbasalt plastic; structural timber works; prestressed reinforcement